Partitioning β-diversity Reveals That Invasions and Extinctions Promote the Biotic Homogenization of Chilean Freshwater Fish Fauna - Pizarro-Konczak, J; Castro-Morales, S (Public Library of Science, 2020)
Aim Exotic species’ introductions together with extinction of native species represent the main mechanisms driving biotic homogenization of freshwater fish assemblages around the world. While generally ichtyofaunistic realms transit towards biotic homogenization, for conservation purposes it is essential to understand what specific mechanisms are promoting it on particular areas or regions. Here, we report the occurrence of biotic homogenization in 29 Chilean watersheds, analyzing its β-diversity (including turnover and nestedness) and predicting future trends. Location Continental Chile (18o–56o S). Methods We determined fish composition per basin for historical and current assemblages; extant native, exotic, and extinct species were recorded as 1 (presence) or 0 (absence) in two matrices basins × species. For each matrix, we calculated the turnover (βsim), nestedness (βnes), and β-diversity (βsor); then, we obtained Δβsim, Δβnes, and Δβsor, as the arithmetical difference between basin pairs over time. In addition, we search for explanatory variables correlating Δβsim, Δβnes, and Δβsor with geographical and land use variables. Finally, simulating events of species introduction (i.e., invasion) and extinction, we generated 15 hypothetical assemblages, looking to establish future trends towards biotic change in Chilean basins. Results Species turnover and β-diversity significantly decreased from historical to current assemblages (Δβsim = -0.084; Δβsor = -0.061, respectively), while the species nestedness did not show significant changes (Δβnes = 0.08). Biotic changes have been driven mainly by the introduction of 28 exotic species, with a minor role of extinctions (one species) and translocations (0 species) of native species. Changes in β-diversity were negatively correlated with area, elevation, and geographical distance between basins but not with land-use nor human population. Finally, the analysis of 15 future assemblages predicts a significant decrease of β-diversity and turnover, and an increase for species nestedness, this time promoted by an increase in the extinction of native species. Main conclusion Chilean basins show a significant decrease of the distributional β-diversity and species turnover of the freshwater fish fauna, evidencing a trend towards biotic homogenization. This trend is shared with other Neotropical basins; however, specific mechanisms driving it show different magnitude. Changes in the β-diversity components do not show correlation with variables associated to land use, thus suggesting that casual introductions of freshwater fishes in Chile follow an opportunistic mode related to commercial use. According to future scenarios simulated, biotic homogenization should increase further, mainly as consequence of increased native extinctions. Copyright: © 2020 Castro et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.